Improving medical outcomes the psychology of doctor-patient visits - Leavitt, Jessica, 1970- (Rowman & Littlefield Publishers, 2011)
"The ability of doctors to properly diagnose and treat patients is often colored by non-specific factors that can affect outcomes in profound ways. Communication between doctors and patients is key, but often what is left unsaid is just as important, and messages from outside sources such as medical journals, drug companies, and other patients can affect how a doctor treats any one patient at any one time. This book outlines the non-specific factors that come into play when doctors and patients interact, how both doctors and patients can overcome these messages to focus in on the health of the person sitting on the table, and how psychological factors in both the doctor and the patient can affect medical outcomes. Anyone hoping to improve the medical care they give or the medical care they get will find in these pages strategies for improving those results"--Provided by publisher.